Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai UINSU, Medan - Sitepu, Abdul Jousef; Siregar, Nina Siti Salmaniah; Hartono, Budi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to analyze the influence of the work environment and work motivation on employee performance at the State Islamic University of North Sumatra, Medan. This type of research is associative quantitative. The population in this research is educational staff with a sample of 56 respondents. Data collection technique with a closed questionnaire which is arranged based on the Likert scale. The research analysis uses multiple linear regression with the help of SPSS 22 software. The results of the study are (1) the work environment has a significant influence on performance because based on the results of the t test a significant level of 0.000 <0.05 is obtained, and the value of t count > t table in One -Tailed, namely 4.462 > 2.05. With a coefficient value of 0.480, it means that if the work environment increases in one unit, it will cause an increase in performance. (2) Work motivation has a significant effect on performance, based on the results of the t test, a significant level of 0.000 <0.05 is obtained and the value of t count > t table is 6.773 > 2.05 on the Two-Tailed test. With a coefficient value of 0.616, it means that if work motivation rises in one unit, it will also cause an increase in performance. (3) Work environment and work motivation have a significant effect simultaneously on performance.